Assessment of Antimicrobial Prescribing Pattern in the Outpatient Department of Ophthalmology in a Tertiary Care Hospital of Western Uttar Pradesh, India - Jain, Amit Kumar; Naimi, Shahzar; Jain, Seema (Nepalese Journal of Ophthalmology, 2018)
Introduction: Assessment of prescribing pattern at regular interval is essential to avoid inappropriate use of drugs, especially of antimicrobial drugs. Objectives: The present study was performed to evaluate the prescribing pattern of antimicrobial drugs in the Ophthalmology Out-Patient Department (OPD) of Santosh Medical College and Hospital, Ghaziabad, India. Material and method: The present study included a total 600 prescriptions of patients attending OPD. A structured proforma was used to record all necessary information of each patient including demographic profi le of patient, diagnosis, total number of drugs and antimicrobials prescribed, group of antimicrobial prescribed, the percentage of antimicrobials prescribed by generic name etc. Results: Total 600 prescriptions were evaluated. Mean age of the study subjects was 28.4 ± 15.05 years. Total 720 antimicrobials were prescribed and the average number of antimicrobial drugs per prescription was 1.2. Fluoroquinolones were most commonly prescribed antimicrobial drugs followed by aminoglycosides and macrolides. 85% of drugs were prescribed in the form of eye drops while 15% were in the form of an ointment. 1.2% of antimicrobial drugs were prescribed by generic names. Out of total antimicrobials drugs, 420 drugs were in the form of fi xed dose combination. Only 1.6% of drugs were prescribed from National Essential Medicines List (NEML) 2015, India. Conclusion: Most of the antimicrobials were prescribed by brand names which require important consideration to promote rational use of antimicrobial drugs. In addition, the number of drugs prescribed from NEML was very less, indicating the need of sensitization among prescribers for the promotion of rational use of drugs